Humor Therapy: Relieving Chronic Pain and Enhancing Happiness for Older Adults - Mimi M. Y. Tse; Anna P. K. Lo; Tracy L. Y. Cheng; Eva K. K. Chan; Annie H. Y. Chan; Helena S. W. Chung (Journal of Aging Research)
The present study examined the effectiveness of a humor therapy program in relieving chronic pain, enhancing happiness and life satisfaction, and reducing loneliness among older persons with chronic pain. It was a quasiexperimental pretest-posttest controlled design. Older persons in a nursing home were invited to join an 8-week humor therapy program (experimental group), while those in another nursing home were treated as a control group and were not offered the program. There were 36 older people in the experimental group and 34 in the control group. Upon completion of the humor therapy program, there were significant decreases in pain and perception of loneliness, and significant increases in happiness and life satisfaction for the experimental group, but not for the control group. The use of humor therapy appears to be an effective nonpharmacological intervention. Nurses and other healthcare professionals could incorporate humor in caring for their patients.